KEBERADAAN Lawana candida (NGENGAT PUTIH) PADA TEGAKAN Casuarina equisetifolia (CEMARA UDANG) DI PANTAI SAMAS, BANTUL, YOGYAKARTA - , SUFI INDRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Shrimp pine (Casuarina equisetifolia) is one type of tree that can grow and control problems of a sandy beach area, resistant to drought conditions, high salinity, flooding and high wind speeds, capable of growing on marginal soils and sandy. This study aims to determine the pest status Lawana candida by wide spread and intensity of the presence of this pest in pine stands shrimp. This study was conducted in May and July 2013. Sites for this research in pine plantation shrimp in Samas Beach, Bantul, Yogyakarta. Research using by survey methods at each age by each crop plantings made 6 field plots with a size of 20 x 20 m. Every tree in the same plot, evergreen plants categorized into 2 shrimp that grow in shaded and open. The mean value of broad distribution and the presence of L. candida intensity of each crop was calculated using MS Excel. From the research broad dissemination of research results (LS) and the intensity of existence (IP) on planting spruce L. candida. shrimp have a similar pattern